Global distribution of seamounts from ship-track bathymetry data - Hillier, J; Watts, A (2007)
The distribution of submarine volcanoes, or seamounts, reflects melting within the Earth and how the magma generated ascends through the overlying lithosphere. Globally (±60° latitude), we use bathymetry data acquired along 39.5 × 106 km of ship tracks to find 201,055 probable seamounts, an order of magnitude more than previous counts across a wider height-range (0.1 < h < 6.7 km). In the North Pacific, seamounts' spatial distribution substantially reflects ridge-crest conditions, variable on timescales of 10 s of Ma and along-ridge distances of ∼1,000 km, rather than intraplate hot-spot related volcanic activity. In the Atlantic, volcano numbers decrease, somewhat counter-intuitively, towards Iceland suggesting that abundant under-ridge melt may deter the formation of isolated volcanoes. Neither previously used empirical curve (exponential or power-law) describes the true size-frequency distribution of seamounts. Nevertheless, we predict 39 ± 1 × 103 large seamounts (h > 1 km), implying that ∼24,000 (60%) remain to be discovered. Copyright 2007 by the American Geophysical Union.